Tissue selection and optimization of DNA extraction for the construction of genomic library of white dragon fruit (Hylocereus undatus) / Loo Zhang Xin - Loo, Zhang Xin (2011)
Genomic library of Hylocereus undatus was successfully constructed using Lambda Bacteriophage FIX II vector kit (Stratagene) which resulted in titer of 4 x 104 pfu/ml. One week old leaflets from seed germination were used for DNA extraction. This method ensures sustainable supply of material for DNA extraction and the yield of the DNA was 975 μg/g of leaf material. The white colour pellet indicates that it was free from contaminants which were supported by a spectrophotometer reading (A260 nm/A280 nm ratio of 1.92) and agarose gel electrophoresis showing intact genomic DNA. The genomic DNA was digested with BamHI to produce fragments within 9-23kb due to the limitation of the vector cloning capacity. BamHI cleaves at the recognition sequence GGATCC which generates an overhang 5’–GATC-3’ molecule. This overhang molecule has to be treated further by partial fill-in reaction according to the Klenow Fill-In Kit (Stratagene). This kit uses Klenow polymerase with the fill-in buffer, dATP and dGTP, because the Lambda FIX II vector (Stratagene) had been digested with XhoI enzyme and partially filled in with dCTP and dTTP leaving 3’-CT-5’ overhangs. This will generate compatible end and prevent it from self ligate. In the partial digestion, 0.30U was identified as the best concentration for the digestion of 1μg of genomic DNA. The digested DNA insert was ligated to the vector at 4°C and subsequently packaged to form virus particles using Gigapack III XL Packaging Extract, an in vitro packaging extract which is specially designed for use in constructing genomic library. It preferentially size selects for extra large insert and thus eliminates the step to size select the genomic insert and avoid the losses of genomic samples through purification. The system operates based on spi (sensitive to P2 inhibition) selection. Lambda phages containing active red and gam genes on the stuffer fragment are unable to grow on host strains that contain P2 phage lysogens such as XL1-Blue MRA (P2). When the stuffer fragment is replaced by an insert, the recombinant Lambda FIX II vector becomes Red–/Gam–, and the phage is able to grow on the P2 lysogenic strain. Hence, in the Lambda FIX II system, only recombinant phages are allowed to grow. Similar strategy to construct the Oryza sativa L. Var. Pokkali and identify their gene of interest with the use of probes. However, the genomic information reported here was obtained using PCR method. The insert DNA was flanked by T7 and T3 promoter (5’-AAT ACG ACT CAC TAT AG-3’ and 5’- ATT AAC CCT CAC TAA AG-3’). Therefore, polymerase chain reaction (PCR) can be used to amplify the insert DNA and send to sequencing centre to process.